Effect of supervised training therapy on pulmonary arterial compliance and stroke volume in severe pulmonary arterial hypertension and inoperable or persistent chronic thromboembolic pulmonary hypertension - Nagel, Christian; Benjamin, Nicola; Egenlauf, Benjamin; Eichstaedt, Christina; Fischer, Christine; Palevičiūtė, Eglė; Čelutkienė, Jelena; Harutyunova, Satenik; Mayer, Eckhard; Nasereddin, Mohammed; Marra, Alberto M.; Grünig, Ekkehard; et al. (Respiration, 2021)
Pulmonary arterial compliance (PAC) is a prognostic parameter in pulmonary arterial hypertension (PAH) reflecting the elasticity of the pulmonary vessels. The objective of this post hoc analysis of a prospective randomized controlled trial (RCT) was to assess the effect of exercise training on PAC and stroke volume (SV) in patients with PAH and persistent/inoperable chronic thromboembolic pulmonary hypertension (CTEPH). From the previous RCT, 43 out of 87 patients with severe PAH (n = 29) and CTEPH (n = 14) had complete haemodynamic examinations at baseline and after 15 weeks by right heart catheterization and were analysed (53% female, 79% World Health Organization functional class III/IV, 58% combination therapy, 42% on supplemental oxygen therapy, training group n = 24, and control group n = 19). Medication remained unchanged for all patients. Results: Low-dose exercise training at 4-7 days/week significantly improved PAC (training group 0.33 ± 0.65 mL/mm Hg vs. control group −0.06 ± 1.10 mL/mm Hg; mean difference 0.39 mL/mm Hg, 95% confidence interval [CI] 0.15-0.94 mL/mm Hg; p = 0.004) and SV (training group 9.9 ± 13.4 mL/min vs. control group −4.2 ± 11.0 mL/min; mean difference 14.2 mL, 95% CI 6.5-21.8 mL; p < 0.001) in the training versus control group. Furthermore, exercise training significantly improved cardiac output and pulmonary vascular resistance at rest, peak oxygen consumption, and oxygen pulse. Our findings suggest that supervised exercise training may improve right ventricular function and PAC at the same time. Further prospective studies are needed to evaluate these findings.
Gesehen am 26.07.2021